79 Evaluation of extended release eprinomectin efficacy on multiparous beef cow performance - Zammit, Laine (J Anim Sci, 2020)
Internal parasitism inevitability prompts economic loss in beef cattle production by decreasing growth performance and reproductive traits. Previous studies have conflicting results on the macrocyclic lactones (ML) efficacy against internal parasitism. The objective of this study was to evaluate the efficacy of milbeymycin and avermectin sub groups of ML on cow performance. Multiparous fall calving, crossbred beef cows (n = 106) were allocated randomly to 1 of 3 anthelmintic treatments: 1) Negative control (CON), in which cows did not receive an anthelmintic, 2) Injectable moxidectin (MOX) and 3) Injectable extended release eprinomectin (ERE). Body weights (BW), body condition scores (BCS), and fecal egg counts (FEC) were taken throughout the duration of the calving season to weaning on d0, d80, d162, and d217, with weaning occurring on d217. Performance data were analyzed using the MIXED procedures of SAS, and pregnancy data were analyzed using the GENMOD procedures of SAS. Significance was fixed at P < 0.05 and tendencies were established from 0.05 ≤ P ≤ 0.10. There was no effect of anthelmintic treatment on cow BW (P ≥ 0.57) or cow BCS (P ≥ 0.22) during the 217 d study; however, CON cows tended to have lower BCS (P = 0.08) throughout the duration of the study. Cows treated with ERE had fewer FEC compared to MOX and CON groups (P ≤ 0.001), and tended to improve pregnancy rates (c(2) = 0.0546). Calf weaning weight was similar among treatments averaging 216, 225, and 223 kg regarding CON, MOX, and ERE cow treatments, respectively.